2017
DOI: 10.18632/oncotarget.23188
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of PLK1 and RAS in hepatocellular carcinoma reveal rigosertib as promising novel therapeutic “dual-hit” option

Abstract: Inhibition of RAS-RAF-ERK-signaling is a major mechanism mediated by the multi-kinase inhibitors sorafenib and regorafenib, the only effective therapeutic approaches for advanced hepatocellular carcinoma (HCC). This underlines the importance of RAS-RAF-ERK-signaling in HCC. Most RAS isoforms were not yet described to play crucial roles in HCC. However, several studies indicate that the HRAS isoform can function as potent oncogene in HCC, but pharmacologic RAS inhibition has not yet been investigated. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 60 publications
(89 reference statements)
2
30
1
Order By: Relevance
“…Many oncogenes, growth factors, and tumor suppressor genes have been identified in processes of hepatocarcinogenesis 22 25 , however, the molecular carcinogenic mechanisms and the pathogenic biology of HCC remains unclear 22 , 26 – 28 . A growing amount of experimental evidence has been supporting a significant role for miRNAs in tumorigenesis of HCC 27 , 29 , 30 .…”
Section: Disscussionmentioning
confidence: 99%
“…Many oncogenes, growth factors, and tumor suppressor genes have been identified in processes of hepatocarcinogenesis 22 25 , however, the molecular carcinogenic mechanisms and the pathogenic biology of HCC remains unclear 22 , 26 – 28 . A growing amount of experimental evidence has been supporting a significant role for miRNAs in tumorigenesis of HCC 27 , 29 , 30 .…”
Section: Disscussionmentioning
confidence: 99%
“…In most recent studies, our group showed that the wild-type RAS isoform Kirsten rat sarcoma (KRAS) is a promising candidate diagnostic and therapeutic target majorly contributing to acquired resistance to RAF inhibitors in HCC and other types of cancer [9], [10], [11]. Moreover, we found that the HRas proto-oncogene (HRAS) isoform is upregulated in HCC and affects patient outcome [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that PLK1 was closely associated with RAS/MEK/ERK pathways, including regulation of MEK1/2 and proliferation in airway smooth muscle cells, 36 induction of epithelial-to-mesenchymal transition and promotion of epithelial cell motility by activating CRAF/ERK signaling, 37 and activation by RAS-RAF signaling as a therapeutic target in HCC. 38 As a result, we explore the relationship between PLK1 and RAS/MEK/ERK in GC. The Western blotting and in vivo assays demonstrated the inhibition of PLK1 activity with BI6727 significantly blocked MEK/ERK phosphorylation and activation, resulting in an obvious reduction in tumor volume and weight.…”
Section: Discussionmentioning
confidence: 99%